2022
DOI: 10.3390/metabo12080720
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Ameliorating Effects of Altered GABA/Glutamate Signaling in a Rodent Model of Autism

Abstract: Autism spectrum disorders (ASDs) comprise a heterogeneous group of pathological conditions, mainly of genetic origin, characterized by stereotyped behavior, such as marked impairment in verbal and nonverbal communication, social skills, and cognition. Excitatory/inhibitory (E/I) imbalances have been recorded as an etiological mechanism of ASD. Furthermore, GABA, the main inhibitory neurotransmitter in adult life, is known to be much lower in both patients and rodent models of ASD. We propose correcting GABA si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Ahmed et al [ 55 ] revealed that the only significant alteration between the GM of ASD children and that of their healthy siblings was the higher abundance of Bifidobacterium in the siblings’ group, supporting its protective role. Several studies have reported various species of Bifidobacterium as GABA (gamma aminobutyric acid) producers [ 56 , 57 ]. GABA is the main inhibitory neurotransmitter in the brain, the concentrations of which have been found to be diminished in ASD children [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al [ 55 ] revealed that the only significant alteration between the GM of ASD children and that of their healthy siblings was the higher abundance of Bifidobacterium in the siblings’ group, supporting its protective role. Several studies have reported various species of Bifidobacterium as GABA (gamma aminobutyric acid) producers [ 56 , 57 ]. GABA is the main inhibitory neurotransmitter in the brain, the concentrations of which have been found to be diminished in ASD children [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ruminococcus are mucosa-associated bacteria linked with gastrointestinal disease, which have been confirmed that altered in ASD patients ( 25 ). In the mice models, bifidobacteria could play a role in the pathogenesis of ASD by modifying the correction of oxidative stress, and restoration of depleted GABA ( 26 ). We are pleased to be able to find alterations in these flora in the treatment, unfortunately, the abundance changes may be biased because this case involved only one patient.…”
Section: Discussionmentioning
confidence: 99%
“…91 The increase in GABA concentrations within the brain of autistic rats after intervention with a single strain and compound strain may be attributed to altered gut microbiota, restoring brain Mg 2+ levels, GABA receptor function, and reducing neurotransmitter glutamate secretion. 92,93 In the negative feedback loop, adipocytes release leptin as an afferent signal. It primarily influences hypothalamic neurons that regulate energy homeostasis and food intake.…”
Section: Gonadotropin-releasing Hormonementioning
confidence: 99%
“…91 The increase in GABA concentrations within the brain of autistic rats after intervention with a single strain and compound strain may be attributed to altered gut microbiota, restoring brain Mg 2+ levels, GABA receptor function, and reducing neurotransmitter glutamate secretion. 92,93…”
Section: Gut–brain–ovary Axismentioning
confidence: 99%